Spiritual Education in Russia: Law and Theology - Lutovinova, Natalya Viktorovna (2021)
It is impossible to imagine modern life without education. It allows a person to learn something new, to know the reality around, to realize their abilities, to reveal their talents, to find a vocation in life. Education is not only the process of learning new information, but it is also the upbringing and development of the individual, their exposure to the world and national culture, the formation of a certain system of values. Currently, there are several problems in education, like in any other public sphere, that cause active discussion in society and require resolution at the legislative level. This article presents a legal study of spiritual education, taking into account its legal regulation and implementation in Russia at the present stage. The authors of the article consider the most important aspects of the implementation of the right to spiritual education in Russia and conduct a comparative legal analysis of the Russian legislation on spiritual education. The article considers the types of educational organizations that provide religious education and their educational programs, describes the foreign experience of religious education, and conducts a systematic analysis of educational standards of higher education. The authors identify current problems in the field of organization and implementation of religious education, give recommendations for their solution, and indicate areas for improving legislation on religious education. It is concluded that the introduction of subjects teaching religion in educational institutions is legal in compliance with the principle of voluntary choice of education.